Obstetric care and the prevention of blindness - Soeprono, Soeprono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
Blindness, affecting multidimensionally the lives of the individual, his family and the society, has been known according to the 1980 Indonesian Population Census to prevail for 22.1% with children and for 77.9% with adults. Based on this fact, causative factors as genetic aberrations, infectious diseases and malnutrition, drugs and radiation, birth traumas and hypertensive diseases ought to be eliminated by all possible measures, e. g. adequate obstetric care starting from the pre-conceptional period, during pregnancy, delivery and in early childhood, by a more healthy pattern of living and nutrition, and a bigger sense of responsibility on the part of both parents. It is thought to be appropriate to base laws and regulations governing social, medical and educational rehabilitation and aid programs on more Adequate medical and functional criteria to better benefit the visually handicapped. Key Words: blindness - obstetric care - genetic diseases - malnutrition - congenital disorders